How robotic surgery is changing our understanding of anatomy - Fabrizio Dal Moro (Taylor & Francis Group, 2018)
The most recent revolution in our understanding and knowledge of the human body is the introduction of new technologies allowing direct magnified vision of internal organs, as in laparoscopy and robotics. The possibility of viewing an anatomical detail, until now not directly visible during open surgical operations and only partially during dissections of cadavers, has created a ‘new surgical anatomy’. Consequent refinements of operative techniques, combined with better views of the surgical field, have given rise to continual and significant decreases in complication rates and improved functional and oncological outcomes. The possibility of exploring new ways of approaching organs to be treated now allows us to reinforce our anatomical knowledge and plan novel surgical approaches. The present review aims to clarify some of these issues. Keywords: Robotic surgery, Anatomy, Laparoscopy, Prostatectomy